2021
DOI: 10.3389/fimmu.2021.643260
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene Enhanced Dermatophagoides Group 1 (Der f 1)-Induced TGFβ1 Signaling Activation Through the Aryl Hydrocarbon Receptor–RhoA Axis in Asthma

Abstract: We have previously demonstrated that benzo(a)pyrene (BaP) co-exposure with dermatophagoides group 1 allergen (Der f 1) can potentiate Der f 1-induced airway inflammation. The underlying mechanism, however, remains undetermined. Here we investigated the molecular mechanisms underlying the potentiation of BaP exposure on Der f 1-induced airway inflammation in asthma. We found that BaP co-exposure potentiated Der f 1-induced TGFβ1 secretion and signaling activation in human bronchial epithelial cells (HBECs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…To investigate the molecular mechanisms underlying the cockroach allergen induced Muc5ac expression, we specifically focused on AhR signaling pathway. Our recent studies have demonstrated that AhR is critical in BaP co-exposure with Der f 1-induced IL-25, IL-33, and TSLP release from airway epithelial cells ( 32 , 33 ). Furthermore, AhR signaling has been shown to regulate the BaP-induced Muc5ac overexpression in airway epithelial cells ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the molecular mechanisms underlying the cockroach allergen induced Muc5ac expression, we specifically focused on AhR signaling pathway. Our recent studies have demonstrated that AhR is critical in BaP co-exposure with Der f 1-induced IL-25, IL-33, and TSLP release from airway epithelial cells ( 32 , 33 ). Furthermore, AhR signaling has been shown to regulate the BaP-induced Muc5ac overexpression in airway epithelial cells ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AhR has been associated with asthma ( 22 26 ) and shown to mediate environmental pollutant-enhanced allergic lung inflammation ( 23 , 27 29 ), ROS-dependent degranulation and activation of mast cells ( 30 , 31 ). We have recently demonstrated that benzo(a)pyrene (BaP, a ubiquitous air pollutant) co-exposure with Der f 1 (a common allergen to human) induced the activation of AhR signaling, which subsequently regulated the co-exposure-induced airway epithelial cell oxidative stress and cytokine release ( 32 , 33 ). Importantly, several studies have suggested that the BaP-induced activation of AhR signaling regulates Muc5ac overexpression in airway epithelial cells ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ras homolog gene family member (RhoA) plays an essential role in the cytoskeleton, maintaining cell morphology, cell migration, and smooth muscle cell contraction. 41 It also plays a key role in many biological activities, such as smooth muscle cell proliferation, cell adhesion, platelet aggregation, contact inhibition, growth, and apoptosis; 42 RhoA /ROCK signaling pathway is co-involved with its downstream effector Rho-associated protein kinase (ROCK), which has been shown to activate when exposed to diabetic kidney cells, 43 some studies have found that FASUDIL treatment inhibits RhoA/ROCK activation and NF-κB nuclear translocation significantly reduces the levels of renal cell adhesion molecule-1 and TGF-β1 proteins 44 and attenuates NF-κB-inflammatory gene upregulation-mediated DN progression. 45 , 46 CDKN1B, also known as cyclin-dependent kinase inhibitor 1B (P27, KIP1), is highly diagnostic in this study of renal tubular injury caused by diabetes, and G1 cells are now thought to be associated with growth inhibition or hypertrophy, cell cycle transitions can be blocked by the cyclin-dependent kinase reactive protein/kinase inhibitor (CIP/Kip) family of cyclin-dependent kinase inhibitors (CKIS: P21, P27, and P57).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AhR has been associated with environmental pollutant-induced allergic airway inflammation (18,(23)(24)(25) and reactive oxygen species (ROS)-dependent mast cell degranulation and activation (26,27). Our previous findings have suggested that benzo(a)pyrene (BaP, a ubiquitous air pollutant) co-exposure with Der f 1 (a common allergen to human) exacerbated AhR signaling pathway that regulates the co-exposure-induced airway epithelial cell oxidative stress and cytokine release (28,29). Furthermore, our recent study demonstrated that epithelial AhR is essential in protecting against cockroach allergeninduced ROS generation, NLRP3 inflammasome activation, and Muc5ac expression (30).…”
Section: Introductionmentioning
confidence: 99%